MEASURES TO IMPROVE BANKS’ INVESTMENT PROCESSES - Юлдашев Erkin Xusanovich; Baltabaev, Maxmud Toshpo‘latovich; Mukhiddinov, Akobirkhon (THE INNOVATION ECONOMY, 2026)
This article provides a comprehensive analysis of measures aimed at improving the investment processes of commercial banks. The study examines the economic nature of bank investment activity, expansion of the resource base, investment risk management, implementation of digital technologies, and optimization of investment portfolios. Based on national and international experience, the role of bank investments in supporting real sector development is substantiated. The research findings offer scientific and practical conclusions aimed at enhancing banks’ investment potential, strengthening financial system stability, and accelerating sustainable economic growth.